Male hypogonadism. Study of five cases - Cerruti, Víctor Lucho (1963)
1. Endocrine - clinical study, laboratory and testicular histology in five patients with male hypogonadism is made . Two . Testicular biopsy is a simple and safe procedure , which should be included routinely in every patient with symptoms or siqnos of hipoqonadismo . Three . This testicular biopsy allows us not only to confirm the clinical diagnosis hypogonadal , but now, while the histolóqíco diagnosis, prognosis and guides evaluates rational therapeutics . April . Thanks to this temperament biopsy has allowed us to identify two patients pre - pubertal testis, Del Castillo syndrome and one case of testicular atrophy probably other conditions had been labeled with the generic term of hypogonadism . May . Also consider that the study of sex chromatin should be systematically performed in every patient with testicular endocrinopathy considering new genetic concepts. 6. In our cases the determination of sex chromatin showed concordance with the phenotype . 7. The incidence of this condition is apparently rare , because few of these patients are included in different clinical entities (Psychiatry , Neurosurgery, etc. . ) As biopsies and frotisis not done routinely in these services . 8. We consider this in frequency of hypogonadism in our environment should be modified as the biopsy and genetic screening is a means incorporated into routine hospital practice and practice.